Preparation of modified polyethersulfone membranes for hemodialysis - Kahraman, Ö. ş.; Phoo, M. T.; Küçük, Ilknur; Hasanoğlu, Ayça (Bulgarska Akademiya na Naukite, 2022)
Polyether sulfone (PES) is one of the common materials used as a membrane in hemodialysis. However, its use in pristine form is limited since its contact with blood can cause various interactions between the membrane and blood cells. Therefore, PES should be modified to reduce these reactions before its use in hemodialysis applications. In this study, tissue and blood-compatible PES based dialysis membranes were prepared by phase inversion method. To improve the biocompatibility and hemo-compatibility of the membrane, the PES polymer was blended with two polymers; polyvinylpyrrolidone (PVP) and polyethyleneglycol (PEG). PES polymer (15% (wt)) in N-methylpyrrolidone was used to prepare the pristine PES membranes while a polymer blend of 5% (wt) PVP or PEG additives and 10% (wt) of PES in the same solvent was used to prepare the modified PES membranes. Biocompatibility and hemo-compatibility of the prepared membranes were defined by water sorption, BSA protein and creatinine adsorption values. The sorption and BSA adsorption experiments indicated that the addition of PVP and PEG in the membrane matrix increased the hydrophilicity of the membrane and decreased the protein adsorption rate. In the light of these results, it was seen that the biocompatibility of the membranes can be increased using PVP and PEG additives in the PES membrane by reducing the amount of protein adsorption, and the modified membranes can prevent complications from contact with blood. © 2022 Bulgarian Academy of Sciences, Union of Chemists in Bulgaria.
Keywords: biocompatible membranes; Hemodialysis; polyether sulfone; polyethylene glycol; polyvinlypyrrolidone